Dynamics of interstate labor migration - Clark, G (Routledge, 1982)
The dynamics of U.S. interstate migration are considered in the light of conventional assumptions regarding regional growth and decline. In-and-out migration are modeled separately using Box-Jenkins techniques, focusing upon the underlying temporal processes (autoregressive, moving average, or some combination of both) and estimated parameters. Gross flows are cross correlated for a selected group of states to establish lead and lag relationships. Analysis indicates that gross migration is subject to distinct fluctuations over the short run, and each set of flows is closely synchronized in time. Differences in parameter estimates and identified processes do, however, exist between growing and declining states. Markovian models are shown to be susceptible to significant error if the labor migration processes are actually moving-average rather than autoregressive structures. Similarly, net migration estimates are shown to be very misleading and subject to significant errors in forecasting.